Removal of taste and odor causing compounds by UV/H2O2 treatment: effect of the organic and inorganic water matrix. Issue 57 (7th December 2016) - Bang, Hohee; Slokar, Yness M.; Ferrero, Giuliana; Kruithof, Joop C.; Kennedy, Maria D.
Abstract: The occurrence of taste and odor in drinking water is the most common cause of consumer complaints. In this study, the effect of water matrix constituents (i.e. TOC, alkalinity, and ) on the removal of geosmin/2-MIB with UV/H2 O2 treatment was assessed. Experiments were carried out with a collimated beam apparatus equipped with a low and a medium-pressure (MP) UV lamp, with UV doses ranging from 300 to 1, 200 mJ/cm 2 with and without the addition of 4 mg/L H2 O2 . Results showed that the removal efficiency of geosmin/2-MIB with low pressure UV/H2 O2 was inversely proportional to both the concentration of TOC and alkalinity in the synthetic water, as both parameters acted as scavengers of OH radicals. In the case of geosmin, the addition of 0.8 mg C/L of fulvic acid decreased the removal efficiency by 30%. The application of MPUV/H2 O2 to water containing resulted in formation of which is also a OH radical scavenger. The presence of scavengers, in particular natural organic matter, causes significant increase in energy requirement due to the strong absorption properties for UV light and high reactivity with OH radicals.